Concentration for locally acting permutations - Luczak, M; Mcdiarmid, C (2003)
Talagrand (Publ. Math. Inst. Hautes Etudes Sci. 81 (1995) 73) gave a concentration inequality concerning permutations picked uniformly at random from a symmetric group, and this was extended in McDiarmid (Combin. Probab. Comput. 11 (2002) 163) to handle permutations picked uniformly at random from a direct product of symmetric groups. Here we extend these results further, to cover more general permutation groups which act suitably 'locally'. © 2002 Elsevier Science B.V.